Self-as-context and depressive symptoms in the general population: A further analysis of the self experiences questionnaire. Current Psychology - Carvalho, Sérgio (2021)
The current study aims to contribute to the psychometric validation of the Self Experiences Questionnaire (SEQ), a measure of self-as-context as conceptualized by Acceptance and Commitment Therapy, and to contribute to a better understanding of the relationship between self-as-context, other psychological flexibility processes, and depressive symptoms. The sample (N = 266; 72.6% women) was obtained through paper-pencil and online collection methods in the general Portuguese population. Confirmatory factor analysis, reliability analyses, and convergent and divergent analyses were conducted. A mediation analysis of the effects of self-as-distinction and self-as-observer on depression symptoms through openness to experience, behavioral awareness, and valued action (while controlling for brooding) was performed using PROCESS. Items 8, 12 and 15 were removed to achieve the best model fit, which resulted in a 12-item final version of the SEQ. This version appears to be a psychometrically valid two-dimensional measure of self-as-distinction and self-as-observer, as well as a one global measure of self-as-context. Results from mediation analyses suggested that the relationship of self-as-observer and self-as-distinction with depressive symptoms is mediated by the ability to be behaviorally aware and to act according to personal values, but not by the ability to be open to experience. The behaviorally-oriented aspects of psychological flexibility seem to have particular importance on the presentation of depressive symptoms. More studies are nonetheless needed to analyze SEQ’s structure and validity in order to attain a consensual version of the questionnaire.